2020
DOI: 10.3390/jmse8030194
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor Site Characterization for a Remote Island OWC Device Near King Island, Tasmania, Australia

Abstract: We present findings from a geotechnical survey for a gravity-based Wave Energy Converter (WEC) to be installed in King Island, Tasmania. The goal of this work was to assess the deployment location for a 200 kW Oscillating Water Column (OWC) and to identify possible challenges for the foundation of the structure to make it Australia’s first operational offshore OWC for a remote offshore island. The proposed location for this OWC is the southeast coast of King Island, Tasmania, approximately in a depth of ~5.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, this method does not replace the usefulness of core samples, or laboratory sediment investigations as only the top layer (<20 cm) is able to be penetrated in sandy environments. Yet, this was successfully used in further King Island assessments to determine the homogeneity of non-cohesive sediments within the survey region [27]. The aggregation of data in this method (site-suitability model) is able to go beyond the scope of most standards [7], particularly with the inclusion of ground-truthed core samples within the bedrock interpola- The identification of the most sufficient deployment area is a culmination of condensed field deployments and rigorous data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method does not replace the usefulness of core samples, or laboratory sediment investigations as only the top layer (<20 cm) is able to be penetrated in sandy environments. Yet, this was successfully used in further King Island assessments to determine the homogeneity of non-cohesive sediments within the survey region [27]. The aggregation of data in this method (site-suitability model) is able to go beyond the scope of most standards [7], particularly with the inclusion of ground-truthed core samples within the bedrock interpola- The identification of the most sufficient deployment area is a culmination of condensed field deployments and rigorous data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst multiple previous studies have focused on the energy conversion efficiency or internal flow patterns of gravity based OWC WECs [2,4,5], little research has been undertaken on the effects of an OWC WEC on its surrounding environment, and in turn the risks to structure stability or potential reductions in energy efficiency that could occur due to scour (localized sediment erosion) or settlement of the device. This is despite previous site characterization studies for multiple wave energy sites identifying active sediment environments [6,7].…”
Section: Introductionmentioning
confidence: 87%
“…A previous site characterization study at the site by Cossu, et al [7] undertook a sub-bottom profiling analysis to assess the sediment layer thickness at the project site in March 2019 which found that all areas in the survey area had a sediment layer thickness exceeding 1 m. The sediment layer had a thickness of approximately 2-3 m in the area corresponding to Location 1 in Figure 1b. Sand characteristics were also measured in the same study at the site location via dry sieve analysis of retrieved sediment cores.…”
Section: King Island Site and Project Timelinementioning
confidence: 99%
See 1 more Smart Citation
“…In situ measurements of surficial seafloor sediment strength was determined with the BlueDrop penetrometer described by [55,56]. The characteristics of the impact signature were analysed to obtain the kind of substrate-soft, medium, and hard substrate-based on the deceleration curves after impact.…”
Section: Penetrometermentioning
confidence: 99%